2011
DOI: 10.7498/aps.60.024217
|View full text |Cite
|
Sign up to set email alerts
|

Fabry-Perot resonance on extraordinary transmission through one-dimensional metallic gratings with sub-wavelength under transverse electric wave excitation

Abstract: The transmission distribution of transverse electric wave (TE) through one-dimensional metallic gratings with sub-wavelenghth slits with dielectric added in different positions has been simulated by the FDTD (finite difference time domain) method, the extraordinary transmission can be produced at several special wavelengths. The simulation shows that the guided-mode-like resonance theory is the main reason giving rise to the first peak and the second peak. Based on the guided-mode-like resonance theory, from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Increasing substrate thickness, the wavelength of the TM polarization transmittance peak shifts to the right. This can be explained according to F-P-like resonance theory, for TM wave, when + = 2 ( = ℎ 1 + ℎ 2 , N is a positive integer, λg is the wavelength) [11], the polarization transmittance reaches its maximum value. In addition, it can be seen from the formula that the length of the F-P-like cavity is also affected by the grating substrate δ, that is, adding a substrate to the grating will make the cavity length longer.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing substrate thickness, the wavelength of the TM polarization transmittance peak shifts to the right. This can be explained according to F-P-like resonance theory, for TM wave, when + = 2 ( = ℎ 1 + ℎ 2 , N is a positive integer, λg is the wavelength) [11], the polarization transmittance reaches its maximum value. In addition, it can be seen from the formula that the length of the F-P-like cavity is also affected by the grating substrate δ, that is, adding a substrate to the grating will make the cavity length longer.…”
Section: Resultsmentioning
confidence: 99%
“…Novel spoof surface plasmon polaritons (SPPs) in perfect electrical conductors have been identified as an alternative mechanism for achieving EOT, extending its applicability beyond transverse magnetic (TM) modes [18][19][20]. Initially attributed to the presence of surface plasmon polaritons (SPPs), which are predominantly excited by transverse magnetic (TM) waves, recent studies have demonstrated the possibility of EOT for transverse electric (TE) waves as well [21][22][23][24][25][26]. Notably, some researchers have successfully realized EOT in configurations that accommodate both TM and TE waves at the same wavelength, as supported by theoretical analyses, numerical simulations, and experimental observations [27][28][29].…”
Section: Introductionmentioning
confidence: 99%